Do early responders and treatment non‐responders offer guidance to make CPT group a more effective treatment?. Issue 7 (16th February 2022) - Williams, M. Wright; King‐Casas, Brooks; Chiu, Pearl H.; Sciarrino, Nicole; Estey, Matthew; Hunt, Christopher; McCurry, Katherine; Graham, David P.
Abstract: Background: Treatment dropout has been problematic with evidence‐based treatments for posttraumatic stress disorder (PTSD), including cognitive processing therapy (CPT). This study sought to evaluate whether CPT group contributed to symptom improvement among treatment completers and non‐completers. Methods: Sixty‐one Iraq and Afghanistan combat Veterans self‐selected CPT group or treatment as usual (TAU) forming a convenience sample. Defining treatment completion as attending at least nine sessions: 18 completed treatment, 20 dropped‐out (DOs); 20 completed TAU, 3 lost to TAU follow‐up. Results: Multiple Regression revealed significant pre−post‐treatment improvement, the Clinician‐Administered PTSD Scale (CAPS‐IV, F (5,  40.1) = 2.53, p  = 0.0436). Reviewing DOs' last available PTSD Checklist‐Military Version scores before leaving treatment, six achieved clinically significant improvement of >10 points; seven a clinically reliable change of 5−10 points. Conclusion: These findings highlight that CPT group may be effective at reducing trauma‐related symptoms among treatment completers and dropouts and point to the utility of a clinical definition of good treatment end‐state.